Review on data center issues and challenges: Towards the Green Data Center - Bahari H.I.; Shariff S.S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Control systems; Cooling systems; Digital storage; Energy efficiency; Energy management; Energy utilization; Facings; Information management; Natural resources management; Resource allocation; Web services; Additional equipment; Data centers; Green data centers; Internet services; Issues and challenges; IT system; Resource management; Web hosting; Green computing